Effects of the non-peptide, non-selective endothelin antagonist, bosentan, on regional haemodynamic responses to NG-monomethyl-L-arginine in conscious rats. - Gardiner, S. M. (1996)
1. Male, Long Evans rats (350-450 g) were chronically instrumented to allow monitoring of mean arterial blood pressure, heart rate and changes in renal, mesenteric and hindquarters haemodynamics. In the first experiment, animals (n = 8) were given a bolus i.v. injection of the nitric oxide synthase inhibitor, NG-monomethyl-L-arginine hydrochloride (L-NMMA; 30 mg kg-1) on four consecutive days. Fifteen min prior to L-NMMA administration on the fourth day, the endothelin, ETA-, ETB-receptor antagonist, bosentan, was injected (30 mg kg-1, i.v.). Relative to the response on the third day, bosentan caused 33 +/- 4%, 24 +/- 3%, 14 +/- 3%, and 18 +/- 5% inhibition of the pressor, and renal, mesenteric and hindquarters vasoconstrictor effects of L-NMMA, respectively. 2. In the second experiment, bosentan was given 15 min before L-NMMA in a group of rats (n = 6) which had not received L-NMMA previously. Relative to the responses to L-NMMA on the first day in the previous experiment, bosentan caused a 30%, 24%, 18% and 27% inhibition of the pressor, and renal, mesenteric and hindquarters vasoconstrictor effects of L-NMMA, respectively. 3. The results indicate a significant contribution from endothelin to the haemodynamic effects of L-NMMA in conscious rats. However, since our previous studies have shown the renin-angiotensin and sympathoadrenal systems are not involved, it is likely that the major component of the cardiovascular response to L-NMMA in conscious rats is due to loss of vasodilator action of endothelial nitric oxide.